Scheuermann’s Disease: A Narrative Review of Treatment Standards - Ćwiek, Hubert Jarosław; Kołodziej-Sieradz, Marta; Terlecka, Anna Magdalena; Gryz, Paulina Klaudia; Komorowski, Kacper; Pilarska, Karolina Jolanta; Szwankowska, Anna Aleksandra; Baczyńska, Anna; Boruszczak, Błażej; Rożenek, Adam Wiktor (Quality in Sport, 2026)
Background. Scheuermann's disease is a structural spinal deformity characterised by thoracic or thoracolumbar hyperkyphosis, defined by anterior wedging of ≥5° across three or more contiguous vertebrae, Schmorl's nodes, and endplate irregularities. Incidence ranges from 0.4% to 10% in adolescents. The atypical form shows higher prevalence among young athletes. Aim. The purpose of this article is to evaluate and summarise the current state of knowledge regarding Scheuermann's disease. Material and methods. A narrative literature review was conducted using Google Scholar, PubMed, Springer Link, and Scopus, with keywords related to Scheuermann's disease. English-language articles from September 2015 to January 2026 were included, with exceptions for historical sources. Results. The natural course is mostly benign. Conservative treatment, comprising of physiotherapy, bracing, and analgesia, aims to halt progression, reduce pain, and improve posture, with bracing achieving approximately 50% correction and major pain improvement. Surgical treatment, standardised as a posterior approach, offers adequate correction with fewer complications than anterior-posterior approach. The key complication is junctional kyphosis. Sports participation is permitted post-treatment, as tolerated. Conclusions. Scheuermann's disease is an important cause of juvenile thoracic hyperkyphosis, with persisting gaps in etiology, diagnostics, and management. Most patients lead normal lives. Conservative treatment is sufficient in most cases, with surgery reserved for patients that didn’t respond to initial measures. Deformity progression is reported in long-term observations, regardless of treatment.